Timing of VV‐ECMO therapy implementation influences prognosis of COVID‐19 patients. Issue 3 (1st February 2021) - Giraud, Raphaël; Legouis, David; Assouline, Benjamin; De Charriere, Amandine; Decosterd, Dumeng; Brunner, Marie‐Eve; Moret‐Bochatay, Mallory; Fumeaux, Thierry; Bendjelid, Karim
Abstract: Introduction: Current knowledge on the use of extracorporeal membrane oxygenation (ECMO) in COVID‐19 remains limited to small series and registry data. In the present retrospective monocentric study, we report on our experience, our basic principles, and our results in establishing and managing ECMO in critically ill COVID‐19 patients. Methods: A cohort study was conducted in patients with severe acute respiratory distress syndrome (ARDS) related to COVID‐19 pneumonia admitted to the ICU of the Geneva University Hospitals and supported by VV‐ECMO from March 14 to May 31. The VV‐ECMO implementation criteria were defined according to an institutional algorithm validated by the local crisis unit and the Swiss Society of Intensive Care Medicine. Results: Out of 137 ARDS patients admitted to our ICU, 10 patients (age 57 ± 4 years, BMI 31.5 ± 5 kg/m 2, and SAPS II score 56 ± 3) were put on VV‐ECMO. The mean duration of mechanical ventilation before ECMO and mean time under ECMO were 7 ± 3 days and 19 ± 11 days, respectively. The ICU and hospital length of stay were 26 ± 11 and 35 ± 10 days, respectively. The survival rate for patients on ECMO was 40%. The comparative analysis between survivors and non‐survivors highlighted that survivors had a significantly shorter mechanical ventilation duration before ECMO (4 ± 2 days vs. 9 ± 2 days, p = 0.01). All the patients who had more than 150 h of mechanical ventilation before the application of ECMO ultimately died. Conclusion: The present results suggest that VV‐ECMO can be safely utilized in appropriately selected COVID‐19 patients with refractory hypoxemia. The main information for clinicians is that late VV‐ECMO therapy (i.e., beyond the seventh day of mechanical ventilation) seems futile. Abstract : Time‐course of COVID‐19 pneumoniafrom the onset of symptoms to the decision to implement VV‐ECMO according to the results of this study. HFNO, high‐flow nasal oxygen; CPAP, continuous positive airway pressure